Rheumatoid arthritis and polymyalgia rheumatica occurring after immune checkpoint inhibitor treatment. Issue 10 (9th June 2017) - Belkhir, Rakiba; Burel, Sébastien Le; Dunogeant, Laetitia; Marabelle, Aurélien; Hollebecque, Antoine; Besse, Benjamin; Leary, Alexandra; Voisin, Anne-Laure; Pontoizeau, Clémence; Coutte, Laetitia; Pertuiset, Edouard; Mouterde, Gaël; et al.
Abstract : Objectives: Immune checkpoint inhibitors (ICIs) targeting cytotoxic T-lymphocyte-associated protein 4 and programmed cell death protein 1 (PD-1) have demonstrated improved survival for multiple cancers. However, these new drug classes have led to increased immune-related adverse events (IrAE). Rheumatic IrAEs have not been well described in clinical trials. We report here cases of rheumatoid arthritis (RA) and polymyalgia rheumatica (PMR) occurring after ICI treatment. Methods: This was a retrospective study of patients receiving an ICI in whom symptoms of arthritis or arthralgia developed and revealed a diagnosis of RA or PMR. Results: In 10 patients who received ICI therapy (all anti-PD-1 or anti-PDL1 antibodies), RA or PMR developed at a median of 1 month (1 to 9) after exposure. No patient had pre-existing rheumatic or autoimmune disease. RA developed in six patients; all six were positive for anti-cyclic citrullinated peptide (anti-CCP) antibodies and four for rheumatoid factor. Anti-CCP antibodies were detected in two out of three patients tested before immunotherapy. Disease-modifying antirheumatic drugs were needed for three patients; the three others received corticosteroids or non-steroid anti-inflammatory drugs. PMR was diagnosed in four patients, all responded to corticosteroids. Despite these IrAEs, immunotherapy was pursued for all but one patient until cancer progression. Conclusions: This is the first description of RA occurring after ICI therapy for cancer. PMR can also occur after ICI, particularly after anti-PD-1 therapy. All cases responded to corticosteroids or with immunosuppressive therapy. Collaboration between rheumatologists and oncologists is crucial and could lead to better recognition and care of these patients.